Efeitos da irradiação com laser de baixa potência (LLLT) em neutrófilos maduros cultivados ex vivo e in vitro na infecção experimental por Paracoccidioides brasiliensis. - Gomes, Bruno José Nascimento (2021)
Paracoccidioidomycosis (PCM) is a severe systemic granulomatous disease, endemic to the Latin American region, caused by thermodimorphic fungi of the Paracoccidioides brasiliensis complex and P. lutzii. Protective immunity is mediated by macrophages and cytokines produced by Th1 and Th17 lymphocytes. PCM is characterized by the inflammatory infiltrate of polymorphonuclear neutrophils (PMNs), which fights fungi via production of reactive oxygen species (ROS) and pro-inflammatory cytokines. It has been reported that the stimulation of PMNs with low potency LASER (LLLT) increased the fungicidal capacity of these cells against Candida albicans and P. brasiliensis. However, it is not yet established where and how LLLT operates. Within context were evaluated, the generation of total oxidizing species and hydrogen peroxide, catalase enzyme activity, cytokine production, protein generation and fungicidal capacity of mature PMNs from subcutaneous air pouch exudates from mice infected with the virulent strain Pb18 of P. brasiliensis and cultivated ex vivo and in vitro. PMNs treated with LLLT dissipate greater cell viability, production of total oxidizing species, H2O2, catalase activity and protein production; as well as an increase in the expression of pro-inflammatory cytokines and a decrease in anti-inflammatory ones. Irradiated PMNs also increase the fungicide's capacity. The results obtained suggest that LLLT can increase PMN metabolism, making these cells more competent in their antifungal activity, as well as modulating the expression of pro-inflammatory and anti-inflammatory cytokines.